What Are the Functions of Chitin Deacetylases in Aspergillus fumigatus? - Mouyna, Isabelle; Dellière, Sarah; Beauvais, Anne; Gravelat, Fabrice; Snarr, Brendan; Lehoux, Mélanie; Zacharias, Caitlin; Sun, Yan; de Jesus Carrion, Steven; Pearlman, Eric; Sheppard, Donald C.; Latgé, Jean-Paul (Frontiers in Cellular and Infection Microbiology, 2020)
Deacetylation of chitin by chitin deacetylases (Cda) results in the formation of chitosan. Chitosan, a polymer of β1,4 linked glucosamine, plays multiple roles in the function of the fungal cell wall, including virulence and evasion of host immune responses. In this study, the roles of chitosan and putative CDAs in cell wall structure and virulence of Aspergillus fumigatus were investigated. Low levels of chitosan were found in the conidial and cell wall of A. fumigatus. Seven putative CDA genes were identified, disrupted and the phenotype of the single mutants and the septuple mutants were investigated. No alterations in fungal cell wall chitosan levels, changes in fungal growth or alterations in virulence were detected in the single or septuple Δcda1-7 mutant strains. Collectively, these results suggest that chitosan is a minority component of the A. fumigatus cell wall, and that the seven candidate Cda proteins do not play major roles in fungal cell wall synthesis or virulence. However, Cda2 is involved in conidiation, suggesting that this enzyme may play a role in N-acetyl-glucosamine metabolism.